Performance Enhancement of the South Baghdad Thermal Station - Mashi, Hussein Wheeb (Al-Khwarizmi Engineering Journal, 2017)
Aim of the research is the study of improving the performance of the thermal station south Baghdad and the main reasons for reduced its efficiency. South Baghdad power planet comprises (6) steam turbine units and (18) gas turbine units .The gas turbine units are composed of two groups: the first group is made up of gas units (1,2), each of capacity (123) MW. The design efficiency of gas turbine units is 32%. The actual efficiency data of steam units is 18.3% instead of 45% which is the design efficiency. The main reason for efficiency reduction of gas units is the rejected thermal energy with the exhaust gases to atmosphere, that are (450-510) ℃.The bad type of fuel used (heavy) fuel. Another reason for the low efficiency and has a negative impact on the steam and gas units. The actual efficiency that is calculated to set the first group gas unit (1) is (27%). Suppose the steam is passed through the (HRSG) and this (HRSG) passes the combustion products emerging from first group gas turbine unit (1). The temperature of exhaust gases (Tieg =783k) entered (HRSG) and the temperature of gas out from the (HRSG) (Toeg =374k). The thermal efficiency of combined -cycle plant is (the amount of fuel that can be available by using the plant compound in combined cycle, is (3603.88) tons per year. The relationship between the account of load and compression ratio during the three seasons of the year as where a large difference in the degree of heat between summer and winter .When the high temperature in summer less than the energy generated. As was the rate of energy produced is (99.8, 90.6, 70.6) MW in the (winter, autumn and summer), respectively.